COPRECIPITATION OF NI2+, CO2+, AND MN2+ WITH GALENA AND COVELLITE, AND OF SR2+ WITH CALCITE DURING CRYSTALLIZATION VIA DIFFUSION OF H2S AND CO2 THROUGH POLYETHYLENE AT 20OC: POWER LAW AND NERNST LAW CONTROL OF TRACE ELEMENT PARTITIONING - Dietzel M.; Usdowski E. (My University, 1996)
Acanthite (Ag2S), calcite (CaCO3), covellite (CuS), galena (PbS), and sphalerite (ZnS) have been crystallized via the diffusion of H2S or CO2 through polyethylene into metal chloride, metal sulfate or metal nitrate solutions. Coprecipitation experiments show that the incorporation of Co2+, Ni2+, and Mn2+ into galena, and of Ni2+ and Mn2+ into covellite follows a power function. On the other hand, the incorporation of Sr2+ into calcite grown at analogous conditions via the diffusion of CO2 occurs according to the Nernst distribution law. It appears that the free energy for the adsorption of a trace element on the surface of a growing crystal is not necessarily constant but may change as a function of the solute concentration. As either type of partitioning yields different fractionation patterns an example is given which compares the Nernst and the power law partitioning for closed system conditions.